Preparation method and application of mesoporous oxide confinement growth multistage coated perovskite nano-material
The method of growing multi-stage coated perovskite nanomaterials through mesoporous oxides has solved the problem of instability of perovskite materials in harsh environments, achieved high stability and efficient photoconversion performance of the material, and broadened its application prospects in high-end optoelectronic devices.
Patent Information
- Application Number
- CN202411694369.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-07
AI Technical Summary
Due to its inherent instability, perovskite fluorescent conversion materials are prone to hydrolysis, volatility, decomposition and photodegradation under harsh conditions such as humidity, temperature and light, resulting in attenuation of material properties.
The method of growing multi-stage coated perovskite nanomaterials through mesoporous oxides is used to prevent the agglomeration and degradation of perovskite materials through mesoporous oxides, and sealing them through high-temperature/chemical etching strategies to form an oxide coated structure with excellent stability.
It significantly improves the environmental stability and light conversion performance of the material, can maintain long-term stability and high-efficiency performance under high humidity, extreme temperature and strong light conditions, and is suitable for the manufacturing of high-end optoelectronic devices.
Smart Images

Figure CN119570476A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nano-luminescent materials, and specifically to a mesoporous oxide confined growth multi-level coated perovskite nanomaterial and a preparation method thereof, as well as applications in color conversion Micro LEDs and fluorescence conversion photovoltaic cells. Background Art
[0002] Perovskite fluorescent conversion materials can be applied to light conversion devices such as color conversion Micro LED and fluorescent conversion photovoltaic cells due to their excellent luminescence properties. However, the intrinsic instability of perovskite materials restricts their application prospects. For example, perovskite materials are prone to hydrolysis under certain humidity conditions, resulting in the destruction of the crystal structure; under high temperature conditions, the organic components in the perovskite materials may volatilize or decompose, resulting in changes in the material structure and performance degradation; in addition, under long-term illumination, perovskite materials are also prone to photodegradation, which gradually reduces the light conversion efficiency of the material.
[0003] In order to cope with the above material stability challenges, researchers have tried a variety of improvement strategies, including surface passivation of perovskite materials, optimization of material components, and improvement of device packaging processes. However, these methods often have certain limitations, such as passivation treatment is difficult to completely cover the material surface, component optimization may affect the material's light conversion performance, and complex packaging processes increase manufacturing costs and limit the design flexibility of devices.
[0004] In the Chinese patent application "Semiconductor fluorescent composite particles and preparation methods thereof" with application number 202211255720.3, a semiconductor fluorescent composite particle is disclosed, which includes a semiconductor fluorescent material having multiple fluorescent nanocrystals and an oxide material, and the oxide material densely coats the semiconductor fluorescent material. This method can improve the stability of semiconductor fluorescent composite particles and the control of particle size, thereby improving their performance and reliability, but the process of this method is relatively complicated, and the stability of the obtained composite particles under high humidity, extreme temperature and strong light conditions still cannot meet the requirements. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention proposes a preparation method of a mesoporous oxide confined growth multi-level coated perovskite nanomaterial, and provides its application in color conversion Micro LED and fluorescence conversion photovoltaic cells. The method significantly improves the environmental stability of the material by confining the growth of mesoporous oxide and coating the perovskite nanomaterial multi-level.
[0006] The inventive concept of the present invention is as follows:
[0007] Vacancy-ordered double perovskite A 4 B (II) X6 / AB 2 (II) X 5 / A 2 B (IV) X 6 Due to its different ion combination and crystal structure, it is different from AB (II) X 3 Combining to form a coating or a composite can optimize the band structure, thereby improving the stability and performance of the material in practical applications. The mesoporous oxide material has a highly ordered microporous structure and excellent chemical stability. By confining the perovskite material in the micropores of the mesoporous oxide for growth, the agglomeration and degradation of the material can be effectively prevented. In addition, the mesoporous oxide coating layer provides additional protection for the perovskite material, significantly improving the material's tolerance to moisture, oxygen, temperature and light. Therefore, the present invention uses mesoporous oxide as an adsorbent and adopts a high-temperature calcination method to in-situ confine the growth of vacancy ordered A in the micropores of the mesoporous oxide. 4 B (II) X 6 / AB 2 (II) X 5 / A 2 B (IV) X 6 Double perovskite phase coated AB (II) X 3 Phase perovskite, prepare multi-level coated nano-scale perovskite luminescent materials, and seal them through high temperature / chemical etching strategies to form efficient oxide-coated perovskite materials with excellent stability. Compared with the traditional method of coating semiconductor luminescent materials with oxides, the mesoporous oxide multi-level coated perovskite nanomaterials prepared by this multi-level coating growth strategy not only have adjustable core-shell / energy level structure and better resistance to environmental factors such as humidity, temperature and light, but also retain their excellent light conversion performance, and can be stably dispersed in a variety of good solvents to form stable color conversion fluorescent inks, making its application prospects in the fields of color conversion Micro LED and fluorescence conversion photovoltaic cells broader, especially suitable for high-end device manufacturing with strict requirements on material stability and performance.
[0008] The technical solution of the present invention is:
[0009] The present invention proposes a mesoporous oxide confined growth multi-level coated perovskite nanomaterial, which uniformly grows vacancy-ordered double perovskite A in the micropores of the mesoporous oxide. 4 B (II) X 6 / AB 2 (II) X 5 / A 2 B(IV) X 6 Coated AB (II) X 3 Perovskite material and in-situ sealing to form an oxide-coated structure with excellent stability.
[0010] Further preferred solution, AB (II) X 3 , A 4 B (II) X 6 , AB 2 (II) X 5 , A 2 B (IV) X 6 In the perovskite component, A is one or a mixture of Cs, Rb positive monovalent cations, B is one or more of Pb, Sn, Ge, Cu, Mn transition metal ions or rare earth ions, and X is one or more of Cl, Br, I negative monovalent halogen ions.
[0011] The present invention also provides a method for preparing a mesoporous oxide confined growth multi-level coated perovskite nanomaterial, comprising the following steps:
[0012] Step 1: preparing mesoporous oxide nanomaterials;
[0013] Step 2: Obtaining mesoporous oxide confined growth all-inorganic perovskite nanomaterials by high temperature calcination, including the following processes:
[0014] Step 2.1: Prepare precursor solution;
[0015] Step 2.2: mixing the mesoporous oxide nanomaterial with the precursor solution, so that the mesoporous oxide nanomaterial fully absorbs the perovskite precursor;
[0016] Step 2.3: growing perovskite nanocrystals in the micropores of the mesoporous oxide through a high temperature calcination method to obtain a mesoporous oxide confined growth all-inorganic perovskite nanomaterial;
[0017] Step 3: Seal the obtained mesoporous oxide confined growth all-inorganic perovskite nanomaterial, and wash and dry the sealed material to obtain the mesoporous oxide confined growth multi-level coated perovskite nanomaterial.
[0018] In a further preferred embodiment, the mesoporous oxide nanomaterial in step 1 is SiO prepared by a sol-gel method, a coprecipitation method, a template method or a spray pyrolysis method. 2 、Al 2 O 3 、ZrO 2 、TiO2 Or ZnO oxide nanomaterials, in order to make the prepared mesoporous oxide confined growth multi-level coated perovskite nanomaterials have long-term dispersion stability and controllable printing preparation in the dispersion medium, the size of the mesoporous oxide nanomaterial is about 50 to 200 nm.
[0019] In a further preferred embodiment, in step 2, high temperature calcination is performed by a one-step method, comprising the following process:
[0020] Step 2.1: Compare AX with B (II) X 2 or B (IV) X 4 Dissolved in a hot aqueous solution in a certain proportion to obtain a precursor solution;
[0021] Step 2.2: mixing the mesoporous oxide nanomaterial with the precursor solution, so that the mesoporous oxide nanomaterial fully absorbs the perovskite precursor;
[0022] Step 2.3: Dry the mesoporous oxide nanomaterial that adsorbs the perovskite precursor and grind it into powder. Then, according to the transition temperature of the perovskite material, calcine in steps to decompose the perovskite precursor in the micropores of the mesoporous oxide and form perovskite nanocrystals in situ, thereby obtaining a mesoporous oxide confined growth all-inorganic perovskite nanomaterial.
[0023] In a further preferred embodiment, when the high temperature calcination is carried out by a one-step method, when the molar ratio in step 2.1 is AX:B (II) X 2 =1:2, synthesize AB 2 (II) X 5 Coating AB (II) X 3 ; When the molar ratio in step 2.1 is AX:B (II) X 2 =4:1, synthesize A 4 B (II) X 6 Coating AB (II) X 3 ; When the molar ratio in step 2.1 is AX:B (IV) X 4 =2:1, synthesize A 2 B (IV) X 6 Coating AB (II) X 3。
[0024] In a further preferred embodiment, in step 2, high temperature calcination is performed using a two-step method, including the following process:
[0025] Step 2.1: Replace AX and B(II) X 2 Dissolve in hot water at a molar ratio of 1:1 to prepare AB (II) X 3 A component perovskite precursor solution, as a first precursor solution;
[0026] Then AX and B (II) X 2 The vacancy-ordered double perovskite A was prepared by dissolving it in a hot water solution at a molar ratio of 4:1. 4 B (II) X 6 precursor solution, as the second precursor solution; or AX and B (II) X 2 The molar ratio was 1:2 and dissolved in hot water to prepare the vacancy-ordered double perovskite AB. 2 (II) X 5 precursor solution, as the second precursor solution; or AX and B (IV) X 4 The vacancy-ordered double perovskite A was prepared by dissolving it in a hot water solution at a molar ratio of 2:1. 2 B (IV) X 6 a precursor solution, serving as a second precursor solution;
[0027] Step 2.2: Add the mesoporous oxide nanomaterial to the first precursor solution and continue stirring to allow the mesoporous oxide to adsorb sufficient AB. (II) X 3 Component perovskite precursor; adsorb AB (II) X 3 The mesoporous oxide nanomaterial of the component perovskite precursor is dried and kept at 150° C. for a set time and then cooled to room temperature, and then the powder cooled to room temperature is added to the second precursor solution and continuously stirred;
[0028] Step 2.3: The mesoporous oxide nanomaterial taken out from the second precursor solution is dried and ground into powder, and then according to the transition temperature of the perovskite material, the perovskite precursor is decomposed in the mesoporous oxide microchannels through step-by-step calcination to form perovskite nanocrystals in situ, thereby obtaining a mesoporous oxide confined growth all-inorganic perovskite nanomaterial.
[0029] According to a further preferred embodiment, in step 3, a high-temperature sealing strategy is used to seal the mesoporous oxide confined growth all-inorganic perovskite nanomaterial; the high-temperature sealing strategy is to use high-temperature melting and collapse of the oxide to perform in-situ sealing, or to pre-embed the mesoporous oxide with a low-temperature molten salt and then melt and collapse to perform in-situ sealing.
[0030] In a further preferred embodiment, in step 3, chemical etching is used to seal the pores of the mesoporous oxide confined growth all-inorganic perovskite nanomaterial.
[0031] The present invention also proposes the use of mesoporous oxide confined growth multi-level coated perovskite nanomaterials in the preparation of fluorescent inks, color conversion Micro LEDs and fluorescence conversion photovoltaic cells.
[0032] Compared with the prior art, the present invention has the following advantages:
[0033] 1. The present invention obtains a fluorescent conversion material by multi-stage coating, wherein the first-stage coating is AB (II) X 3 Phase perovskite grows on vacancy-ordered A 4 B (II) X 6 / AB 2 (II) X 5 / A 2 B (IV) X 6 In the double perovskite phase, the other level of coating is perovskite in situ confined growth in mesoporous oxide; the prepared fluorescent conversion material shows remarkable environmental stability under high humidity, extreme temperature and strong light conditions, and can maintain its efficient light conversion performance for a long time;
[0034] 2. Due to A 4 B (II) X 6 / AB 2 (II) X 5 / A 2 B (IV) X 6 With different ion combinations and crystal structures, in the present invention, ABX 3 Combining to form a coating or composite can optimize the band structure, with the lattice mismatch of the two perovskite components less than 15%, thereby improving the stability and performance of the material in practical applications;
[0035] 3. The present invention realizes the confined structure of perovskite material in the micropores of mesoporous oxide, effectively suppresses the hard agglomeration of nanocrystals, and ensures the uniform dispersion and long-term stability of the material in the solution;
[0036] 4. The process of mesoporous oxide confined growth perovskite nanomaterial prepared by the present invention is simple and controllable, and has good repeatability;
[0037] 5. The mesoporous oxide confined perovskite nanomaterial prepared by the present invention still maintains high quantum yield and excellent light conversion capability despite the introduction of confined growth of mesoporous oxide and ceramic coating.
[0038] 6. The material prepared by the present invention can be made into stably dispersed printing ink, and can be applied in high-end fields such as color conversion Micro LED and fluorescence conversion photovoltaic cells through inkjet printing technology. The material exhibits high quantum yield, excellent light stability and long life in the application of color conversion Micro LED and fluorescence conversion photovoltaic cells, and is also suitable for the manufacture of high-performance displays, lasers and light conversion devices.
[0039] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0041] Figure 1 The figure is a flow chart of the preparation method of all-inorganic perovskite nanomaterials grown by confined growth of mesoporous oxides. The specific process and steps are as follows: mesoporous oxides of different sizes are prepared by a sol-gel method, and the mesoporous oxides are added to a precursor solution for synthesizing perovskite materials. After stirring for a certain period of time, sufficient precursor ions are adsorbed, and perovskite nanocrystals are confined to grow in situ in the micropores of the mesoporous oxide by a high-temperature calcination method. Finally, the pores are sealed by a high-temperature / chemical method to obtain a stable composite ceramic / perovskite material with fluorescent emission.
[0042] Figure 2 Mesoporous SiO with different sizes 2 Transmission electron microscopy of nanocrystals shows mesoporous SiO 2 The nanocrystals are spherical as a whole, and due to the different contrast, the micropores in the nanocrystals can be clearly observed, which is conducive to the diffusion of ions into the micropores and the in-situ generation of perovskite nanocrystals.
[0043] Figure 3 For example 1, the mesoporous SiO 2 Coated Cs 4 PbB 6 @CsPbBr 3 Transmission electron microscopy images show that perovskite nanocrystals grow on mesoporous SiO 2 inside the micropores.
[0044] Figure 4 The 200 nm mesoporous SiO with green fluorescence prepared in Example 8 2 Confined growth Cs 4 PbB 6 @CsPbBr 3The actual pictures of nanocrystals under fluorescent light and ultraviolet light show that under fluorescent light, the powder is light yellow-green, and under 365nm ultraviolet light, the powder is bright green fluorescence.
[0045] Figure 5 The 200 nm mesoporous SiO with red fluorescence prepared in Example 9 2 Confined growth Cs 4 PbI 6 @CsPbI 3 The actual pictures of nanocrystals under fluorescent light and ultraviolet light show that under fluorescent light, the powder is light reddish brown, and under 365nm ultraviolet light, the powder is bright red fluorescence.
[0046] Figure 6 is Cs in Example 1 and Example 9 4 PbB 6 @CsPbBr 3 and Cs 4 PbI 6 @CsPbI 3 XRD spectrum of the sample. It can be seen from the XRD spectrum that the product contains both 113 phase and 416 phase perovskite components.
[0047] Figure 7 The 200 nm mesoporous SiO with green fluorescence prepared in Examples 8 and 9 2 Confined growth Cs 4 PbB 6 @CsPbBr 3 and Cs 4 PbI 6 @CsPbI 3 Actual pictures of nanocrystals dispersed in hexane solution under fluorescent light and ultraviolet light show that under fluorescent light, the dispersed solution is uniform as a whole and is light green (dark reddish brown), while under 365nm ultraviolet light, it exhibits bright green fluorescence (red fluorescence).
[0048] Figure 8 The 200 nm mesoporous SiO with green fluorescence in Example 8 2 Confined growth Cs 4 PbB 6 @CsPbBr 3 From the fluorescence attenuation graphs of the nanocrystals when continuously heated at 85 degrees, immersed in aqueous solution, and stored in air for different periods of time, it can be seen that the fluorescent powder has excellent stability, and the overall attenuation of the powder fluorescence is less than 10%.
[0049] Fig. 9 The 200 nm mesoporous SiO with green fluorescence prepared in Example 7 2 Confined growth Cs4 PbB 6 @CsPbBr 3 and Cs with red fluorescence 4 PbI 6 @CsPbI 3 Actual photo of nanocrystals spin-coated on the back of a silicon-based solar cell under fluorescent and ultraviolet light. DETAILED DESCRIPTION
[0050] The purpose of the present invention is to provide a method for preparing a perovskite nanomaterial by in-situ confined growth of a mesoporous oxide and multi-level coating, and the application of the material in color conversion Micro LED and fluorescence conversion photovoltaic cells. The method aims to overcome the shortcomings of existing perovskite materials in environmental stability, significantly improve the stability of the material under harsh conditions such as humidity, temperature and light, while maintaining its excellent light conversion performance, and broaden the application prospects of perovskite materials in high-end optoelectronic devices.
[0051] To achieve the above purpose, the present invention uses mesoporous oxide as a template for confined growth, and converts vacancy-ordered double perovskite A into a nanostructured ... 4 B (II) X 6 / AB 2 (II) X 5 / A 2 B (IV) X 6 Coated AB (II) X 3 The perovskite material grows uniformly in the micropores of the mesoporous oxide, and through high temperature / chemical etching strategies, the pores are sealed in situ to form an oxide-coated structure with excellent stability. The microporous structure of the mesoporous oxide not only provides a confined space for the growth of the perovskite material, but also effectively prevents the agglomeration and degradation of the perovskite material in harsh environments through its good chemical stability, significantly improving the material's service life and light conversion performance.
[0052] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. It should be noted that the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0053] Embodiment 1:
[0054] In this example, 50 nm mesoporous SiO 2As a template for confined growth, the pores are sealed by high-temperature calcination in one step, and the oxide is melted and collapsed at high temperature in situ to achieve the goal of confined growth in mesoporous SiO 2 Confined growth of Cs in microchannels 4 PbB 6 Coated CsPbBr 3 Nanocrystalline composites, the specific process is:
[0055] Step 1: Preparation of 50 nm mesoporous SiO 2 Nanomaterials:
[0056] 2.5g of hexadecyltrimethylammonium bromide was added to 1.2L of deionized water, and the mixture was heated to 80°C to accelerate the dissolution of the surfactant. Subsequently, a 2mol / L sodium hydroxide solution was prepared, and 6.2mL of sodium hydroxide solution was added to the above mixture and stirred evenly. Then, 20mL of tetraethyl orthosilicate was added dropwise to the mixture at 80°C and stirred for 2h. After the reaction was completed, the product was collected by centrifugation and washed three times with deionized water. Finally, the product was vacuum dried at 100°C for 12h, and calcined at 500°C in an air atmosphere for 5h to remove hexadecyltrimethylammonium bromide, and a mesoporous SiO with a size of about 50nm was obtained. 2 powder.
[0057] Step 2: One-step high temperature calcination, including the following processes:
[0058] Step 2.1: Prepare the precursor solution. The specific process is as follows:
[0059] Weigh 10.65g CsBr and 7.34g PbBr 2 , the molar ratio is 5:2 (=4:1+1:1); dissolved in 100 mL of deionized water, and the solution is heated to 80 ° C and stirred until CsBr and PbBr 2 Completely dissolved to obtain a precursor solution.
[0060] Step 2.2: Mixing the mesoporous oxide nanomaterial with the precursor solution so that the mesoporous oxide nanomaterial fully absorbs the perovskite precursor. The specific process is as follows:
[0061] 50 g of mesoporous SiO 2 The powder was added to the precursor solution and stirred for 1 h.
[0062] Step 2.3: growing perovskite nanocrystals in the micropores of the mesoporous oxide nanomaterial by high temperature calcination to obtain a mesoporous oxide confined growth all-inorganic perovskite nanomaterial. The specific process is as follows:
[0063] The mesoporous SiO2 adsorbs the perovskite precursor 2 The sample was placed in an oven at 80°C to evaporate water until a dry sample was obtained. The dried sample was ground into powder, and the temperature was increased to 400°C in a muffle furnace at a heating rate of 5°C / min and calcined for 1 hour. Then, the sample was calcined at 700°C at a heating rate of 10°C / min for 1 hour to obtain a mesoporous oxide confined growth all-inorganic perovskite nanomaterial. The atmosphere conditions during the calcination process were controlled to be an inert gas or a vacuum to inhibit the decomposition and oxidation of the perovskite material.
[0064] Step 3: sealing the obtained mesoporous oxide confined growth all-inorganic perovskite nanomaterial, and washing and drying the sealed material to obtain a mesoporous oxide confined growth multi-level coated perovskite nanomaterial, the specific process is:
[0065] The obtained mesoporous oxide confined growth all-inorganic perovskite nanomaterial was further heated to 750°C in a muffle furnace and maintained for 30 min. The pores were sealed by in-situ high-temperature melting and collapse of the oxide. After naturally cooling to room temperature, the sample was ground and washed three times with deionized water, and finally dried in an oven at 80°C. A 50nm mesoporous SiO2 with green fluorescence emission was obtained. 2 Confined growth Cs 4 PbB 6 Coated CsPbBr 3 Nanocrystalline composites. Due to the calcination process at 750℃, mesoporous SiO 2 The micro-pores are sealed by in-situ high-temperature melting and collapse.
[0066] Embodiment 2:
[0067] In this embodiment, 50nm mesoporous SiO 2 As a template for confined growth, the two-step method is used for high-temperature calcination, and the oxide is melted and collapsed in situ to achieve pore sealing. 2 Confined growth of Cs in microchannels 4 PbB 6 Coated CsPbBr 3 Nanocrystalline composites, the specific process is:
[0068] Step 1: Preparation of mesoporous SiO 2 Nanomaterials, the process is the same as step 1 in Example 1.
[0069] Step 2: Two-step high temperature calcination, including the following process:
[0070] Step 2.1: Prepare the precursor solution. The specific process is as follows:
[0071] Weigh 2.13g CsBr and 3.67g PbBr 2 , the molar ratio is 1:1; dissolved in 100 mL of deionized water, and the solution is heated to 80° C. and stirred until completely dissolved to obtain a first precursor solution;
[0072] Weigh 8.52g CsBr and 3.67g PbBr 2 , the molar ratio is 4:1; dissolved in 100 mL of deionized water, and the solution is heated to 80° C. and stirred until completely dissolved to obtain a second precursor solution.
[0073] Step 2.2: Mixing the mesoporous oxide nanomaterial with the precursor solution so that the mesoporous oxide nanomaterial fully absorbs the perovskite precursor. The specific process is as follows:
[0074] 50 g of mesoporous SiO 2 The powder was added to the first precursor solution and stirred for 1 hour; the mesoporous SiO 2 Place the sample in an oven at 80°C to evaporate the water until a dry sample is obtained. Heat the sample to 150°C and keep it for 3 hours before cooling it to room temperature. Add the powder cooled to room temperature to the second precursor solution and continue stirring for 1 hour.
[0075] Step 2.3: The perovskite nanocrystals are confined and grown in the micro-channels of the mesoporous oxide nanomaterial by a high temperature calcination method to obtain a mesoporous oxide confined growth all-inorganic perovskite nanomaterial. The specific process is as follows:
[0076] The mesoporous SiO 2 The sample was placed in an oven at 80°C to evaporate water until a dry sample was obtained. The dried sample was ground into powder, and the temperature was increased to 400°C in a muffle furnace at a heating rate of 5°C / min and calcined for 1 hour. Then, the sample was calcined at 700°C at a heating rate of 10°C / min for 1 hour to obtain a mesoporous oxide confined growth all-inorganic perovskite nanomaterial. The atmosphere conditions during the calcination process were controlled to be an inert gas or a vacuum to inhibit the decomposition and oxidation of the perovskite material.
[0077] Step 3: Seal the obtained mesoporous oxide confined growth all-inorganic perovskite nanomaterial, and wash and dry the sealed material to obtain a mesoporous oxide confined growth multi-level coated perovskite nanomaterial. The specific process is the same as step 3 in Example 1. Obtain a 50nm mesoporous SiO 2 Confined growth Cs 4 PbB 6 Coated CsPbBr 3 Nanocrystalline composites.
[0078] Embodiment 3:
[0079] Take 20 mg of the green fluorescent confined growth Cs prepared in Example 1 4 PbB 6 Coated CsPbBr 3 The nanocrystal composite was dispersed in 2 mL of ethanol by ultrasonication, and 1.5 mL of ethanol was evaporated by heating to concentrate the product. Then 1 mL of Microchem SU-8 2002 photoresist was added and mixed thoroughly by stirring to prepare 50 nm mesoporous SiO 2 Confined growth Cs 4 PbB 6 Coated CsPbBr 3 Nanocrystalline composite ink.
[0080] Embodiment 4:
[0081] Take an appropriate amount of 50 nm mesoporous SiO prepared in Example 3 2 Confined growth Cs 4 PbB 6 Coated CsPbBr 3 Nanocrystalline composite ink was spin-coated on a PVK-CBP / PEDOT / ITO substrate, and the substrate was baked at 90°C for 2 minutes. Under a specific mask, the thin film on the substrate was exposed to light with a 365nm UV light source for 10 seconds, and then baked again at 90°C for 2 minutes. The film was then immersed in a developer of Microchem SU-8 2002 photoresist for development, then cleaned with isopropanol, and finally dried with nitrogen to obtain a patterned film. Finally, a layer of silver about 100nm thick was deposited on the surface of the film as the top electrode using electron beam evaporation to prepare a green-emitting Micro LED.
[0082] Embodiment 5:
[0083] Take 20 mg of the green fluorescent 50 nm mesoporous SiO prepared in Example 1 2 Confined growth Cs 4 PbB 6 Coated CsPbBr 3 The nanocrystal complex was dispersed in 1 mL of photosensitive resin containing a photoinitiator and stirred in a dark environment until uniformly dispersed to obtain a photosensitive resin nanocrystal solution; a 20×20 mm 2The commercial silicon-based solar cell was prepared by spin coating the photosensitive resin nanocrystal solution at a speed of 3000 r / min on the back of the solar cell; the photosensitive resin was then cured using a 365nm UV lamp, and finally a 100nm thick CaF layer was evaporated on the surface of the nanocrystal composite. 2 As an anti-reflection layer, colorful solar photovoltaic cells with enhanced light conversion capabilities can be prepared.
[0084] Embodiment 6:
[0085] In this embodiment, 50nm mesoporous SiO 2 As a template for confined growth, the mesoporous SiO2 is calcined at high temperature in a two-step method, and the mesoporous oxide is pre-embedded with low-temperature molten salt to achieve in-situ collapse and sealing of the micropores in the mesoporous oxide at a relatively low temperature. 2 Confined growth of Cs in microchannels 4 PbB 6 Coated CsPbBr 3 Nanocrystalline composites, the specific process is:
[0086] Step 1: Preparation of mesoporous SiO 2 Nanomaterials, the process is the same as step 1 in Example 2.
[0087] Step 2: Two-step high temperature calcination, including the following process:
[0088] Step 2.1: Prepare a precursor solution, the process is the same as step 2.1 in Example 2.
[0089] Step 2.2: Mix the mesoporous oxide nanomaterial with the precursor solution to allow the mesoporous oxide nanomaterial to fully absorb the perovskite precursor. The process is the same as step 2.2 in Example 2.
[0090] Step 2.3: Confining the growth of perovskite nanocrystals in the micropores of the mesoporous oxide nanomaterial by a high-temperature calcination method, and pre-burying the mesoporous oxide with a low-temperature molten salt to seal the obtained mesoporous oxide confined growth all-inorganic perovskite nanomaterial at a relatively low temperature, and washing and drying the sealed material to obtain a mesoporous oxide confined growth multi-level coated perovskite nanomaterial. The specific process is as follows:
[0091] The mesoporous SiO 2 Place the sample in an oven at 80 °C to evaporate the water until a dry sample is obtained. Grind the dried sample into powder. Mix the powder with 1.01 g KNO 3 , 0.425 g NaNO 3The product was then transferred to a muffle furnace and heated to 350 °C at a heating rate of 5 °C / min and calcined for 1 h. The product was naturally cooled to room temperature and washed three times with a polar solvent DMF. After drying in an oven, a 50 nm mesoporous SiO2 with green fluorescence emission was obtained. 2 Confined growth Cs 4 PbB 6 Coated CsPbBr 3 Nanocrystalline composites. By adding low-temperature molten salts, the crystallization temperature of perovskite can be greatly reduced, and the mesoporous SiO 2 of micropores.
[0092] Embodiment 7:
[0093] In this example, 50 nm mesoporous SiO 2 As a template for confined growth, it is calcined at high temperature in one step and reacted in situ on the surface of the mesoporous oxide by chemical etching to form an inorganic salt-stable shell structure with a small equilibrium constant, achieving in-situ pore sealing and surface passivation, thereby forming a mesoporous SiO 2 Confined growth of Cs in microchannels 4 PbB 6 Coated CsPbBr 3 Nanocrystalline composites, the specific process is:
[0094] Step 1: Preparation of mesoporous SiO 2 Nanomaterials, the process is the same as step 1 in Example 1.
[0095] Step 2: high temperature calcination is carried out in one step, and the process is the same as that of step 2 in Example 1.
[0096] Step 3: sealing the obtained mesoporous oxide confined growth all-inorganic perovskite nanomaterial, and washing and drying the sealed material to obtain a mesoporous oxide confined growth multi-level coated perovskite nanomaterial, the specific process is:
[0097] The obtained mesoporous oxide confined growth all-inorganic perovskite nanomaterial was ground in a mortar and dispersed in 10 mL of 0.05 mol / L AgNO 3 In aqueous solution, 1 mL of 0.25 mol / L dilute sulfuric acid solution was added dropwise to form the mesoporous SiO 2 A layer of Ag is grown on the surface 2 SO 4 Passivation layer; then remove the mesoporous SiO 2The samples were washed three times with deionized water and finally dried in an oven at 80 °C. 2 Confined growth Cs 4 PbB 6 Coated CsPbBr 3 Nanocrystalline composites.
[0098] Embodiment 8:
[0099] In this example, 200 nm mesoporous SiO 2 As a template for confined growth, the pores are sealed by high-temperature calcination in one step, and the oxide is melted and collapsed at high temperature in situ to achieve the goal of confined growth in mesoporous SiO 2 Confined growth of Cs in microchannels 4 PbB 6 Coated CsPbBr 3 Nanocrystalline composites, the specific process is:
[0100] Step 1: Batch synthesis of 200 nm mesoporous SiO 2 Nanomaterials:
[0101] 2.5 g of hexadecyl trimethyl ammonium bromide was dispersed in 1.2 L of deionized water, and the surfactant was dissolved by heating to 80 ° C to obtain a mixed solution. A 2 mol / L sodium hydroxide solution was prepared, and 0.9 mL of 2 mol / L sodium hydroxide solution was added to the above mixed solution and mixed evenly. 20 mL of tetraethyl orthosilicate was added dropwise to the mixed solution at 80 ° C. The mixed solution was stirred for 6 h, and then the product was collected by centrifugation. The product was washed three times with deionized water, vacuum dried at 100 ° C for 12 h, and calcined at 500 ° C for 5 h in an air atmosphere to remove hexadecyl trimethyl ammonium bromide, and a mesoporous SiO with a size of about 200 nm was obtained. 2 .
[0102] Steps 2 and 3 are the same as those in Example 1, and a 200 nm mesoporous SiO2 with green fluorescence can be obtained. 2 Confined growth Cs 4 PbB 6 Coated CsPbBr 3 Nanocrystalline composites.
[0103] Embodiment 9:
[0104] In this example, 200 nm mesoporous SiO 2 As a template for confined growth, the pores are sealed by high-temperature calcination in one step, and the oxide is melted and collapsed at high temperature in situ to achieve the goal of confined growth in mesoporous SiO 2 Confined growth of Cs in microchannels 4 PbI6 Coated CsPbI 3 Nanocrystalline composites, the specific process is:
[0105] 10.65 g CsBr and 7.34 g PbBr in step 2.1 of Example 8 were added 2 Replace with 13.0g CsI and 9.22g PbI 2 , the molar ratio is 5:2, and other conditions and operations remain unchanged to obtain 200nm mesoporous SiO 2 Confined growth Cs 4 PbI 6 Coated CsPbI 3 Nanocrystalline composites.
[0106] Embodiment 10:
[0107] The 50 nm mesoporous SiO 2 The same mass was replaced with 200nm mesoporous SiO 2 The other steps are the same as those in Example 9, and a 200 nm mesoporous SiO 2 Confined growth Cs 4 PbI 6 Coated CsPbI 3 Nanocrystalline composites.
[0108] Embodiment 11:
[0109] Take 20 mg of the 50 nm mesoporous SiO2 prepared in Example 9 for red fluorescence emission 2 Confined growth Cs 4 PbI 6 Coated CsPbI 3 Nanocrystalline composite, the other steps are the same as those in Example 3, and 50nm mesoporous SiO 2 Confined growth Cs 4 PbI 6 Coated CsPbI 3 Nanocrystalline composite ink.
[0110] Embodiment 12:
[0111] Take 20 mg of the 50 nm mesoporous SiO2 prepared in Example 9 for red fluorescence emission 2 Confined growth Cs 4 PbI 6 Coated CsPbI 3 The nanocrystal composite, the other steps are the same as those in Example 5, and a color solar photovoltaic cell with enhanced light conversion capability can be prepared.
[0112] Embodiment 13:
[0113] In this example, 50 nm mesoporous SiO 2 As a template for confined growth, the two-step method is used for high-temperature calcination, and the oxide is melted and collapsed in situ to achieve pore sealing. 2 Confined growth of Cs in microchannels 2 S N 6 Coated CsPbBr 3 Nanocrystalline composites, the specific process is:
[0114] Step 1: Preparation of mesoporous SiO 2 Nanomaterials, the process is the same as step 1 in Example 1.
[0115] Step 2: Two-step high temperature calcination, including the following processes:
[0116] Step 2.1: Prepare the precursor solution. The specific process is as follows:
[0117] Weigh 2.13g CsBr and 3.67g PbBr 2 , the molar ratio is 1:1; dissolved in 100 mL of deionized water, and the solution is heated to 80° C. and stirred until completely dissolved to obtain a first precursor solution;
[0118] Weigh 4.26g CsBr and 4.38g SnBr 4 , the molar ratio is 2:1; dissolved in 100 mL of deionized water, and the solution is heated to 80° C. and stirred until completely dissolved to obtain a second precursor solution;
[0119] Step 2.2: Mixing the mesoporous oxide nanomaterial with the precursor solution so that the mesoporous oxide nanomaterial fully absorbs the perovskite precursor. The specific process is as follows:
[0120] 50 g of mesoporous SiO 2 The powder was added to the first precursor solution and stirred for 1 hour; the mesoporous SiO 2 Place the sample in an oven at 80°C to evaporate the water until a dry sample is obtained. Heat the sample to 150°C and keep it for 3 hours before cooling it to room temperature. Add the powder cooled to room temperature to the second precursor solution and continue stirring for 1 hour.
[0121] Step 2.3: growing perovskite nanocrystals in the micropores of the mesoporous oxide nanomaterial by high temperature calcination to obtain a mesoporous oxide confined growth all-inorganic perovskite nanomaterial. The specific process is as follows:
[0122] The mesoporous SiO 2 Place it in an oven at 80°C to evaporate the water until a dry sample is obtained. Grind the dried sample into powder, heat it to 400°C in a muffle furnace at a heating rate of 5°C / min and calcine it at 1h. Then, calcine it at 700°C at a heating rate of 10°C / min for 1h to obtain a mesoporous oxide confined growth all-inorganic perovskite nanomaterial.
[0123] Step 3: Seal the obtained mesoporous oxide confined growth all-inorganic perovskite nanomaterial, and wash and dry the sealed material to obtain a mesoporous oxide confined growth multi-level coated perovskite nanomaterial. The specific process is the same as step 3 in Example 1. Obtain a 50nm mesoporous SiO 2 Confined growth Cs 2 S N 6 Coated CsPbBr 3 Nanocrystalline composites.
[0124] Embodiment 14:
[0125] In this example, 50 nm mesoporous SiO 2 As a template for confined growth, the two-step method is used for high-temperature calcination, and the oxide is melted and collapsed in situ to achieve pore sealing. 2 Confined growth of Cs in microchannels 2 SnCl 6 Coated Mn 2+ Doped CsPbCl 3 Nanocrystalline composites, the specific process is:
[0126] Step 1: Preparation of mesoporous SiO 2 Nanomaterials, the process is the same as step 1 in Example 1.
[0127] Step 2: Two-step high temperature calcination, including the following processes:
[0128] Step 2.1: Prepare the precursor solution. The specific process is as follows:
[0129] Weigh 1.68g CsCl and 2.78g PbCl 2 and 0.63 g MnCl 2 , the molar ratio is 2:2:1; dissolved in 100 mL of deionized water, and the solution is heated to 80° C. and stirred until completely dissolved to obtain a first precursor solution;
[0130] Weigh 3.37g CsCl and 2.6g SnCl 4, the molar ratio is 2:1; dissolved in 100 mL of deionized water, and the solution is heated to 80° C. and stirred until completely dissolved to obtain a second precursor solution.
[0131] Step 2.2: Mixing the mesoporous oxide nanomaterial with the precursor solution so that the mesoporous oxide nanomaterial fully absorbs the perovskite precursor. The specific process is as follows:
[0132] 50 g of mesoporous SiO 2 The powder was added to the first precursor solution and stirred for 1 hour; the mesoporous SiO 2 Place the sample in an oven at 80°C to evaporate the water until a dry sample is obtained. Heat the sample to 150°C and keep it for 3 hours before cooling it to room temperature. Add the powder cooled to room temperature to the second precursor solution and continue stirring for 1 hour.
[0133] Step 2.3: growing perovskite nanocrystals in the micropores of the mesoporous oxide nanomaterial by high temperature calcination to obtain a mesoporous oxide confined growth all-inorganic perovskite nanomaterial. The specific process is as follows:
[0134] The mesoporous SiO 2 The sample was placed in an oven at 80°C to evaporate water until a dry sample was obtained. The dried sample was ground into powder, and the temperature was increased to 400°C at a heating rate of 5°C / min in a tubular furnace with a mixed reducing gas of nitrogen and hydrogen (the reducing gas can effectively protect the divalent manganese ions from oxidation), and calcined for 1 hour. Then, the sample was calcined at 700°C at a heating rate of 10°C / min for 1 hour to obtain a mesoporous oxide confined growth all-inorganic perovskite nanomaterial. The atmosphere conditions during the calcination process were controlled to be an inert gas or a vacuum to inhibit the decomposition and oxidation of the perovskite material.
[0135] Step 3: The obtained mesoporous oxide confined growth all-inorganic perovskite nanomaterial is sealed, and the sealed material is cleaned and dried to obtain a mesoporous oxide confined growth multi-level coated perovskite nanomaterial. The specific process is the same as step 3 in Example 1. A 50nm mesoporous SiO2 nanoparticle with red fluorescence emission is obtained. 2 Confined growth Cs 2 SnCl 6 Coated Mn 2+ Doped CsPbCl 3 Nanocrystalline composites.
[0136] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A mesoporous oxide confined growth multi-level coated perovskite nanomaterial, characterized in that: Uniform growth of vacancy-ordered double perovskite A4B in the microchannels of mesoporous oxides (II) X6 / AB2 (II) X5 / A2B (IV) X6 coated AB (II) X3 perovskite material, and in-situ sealing to form an oxide-coated structure.
2. According to claim 1, a mesoporous oxide confined growth multi-level coated perovskite nanomaterial, characterized in that: AB (II) X3、A4B (II) X6, AB2 (II) X5, A2B (IV) In the X6 perovskite component, A is one or a mixture of Cs and Rb positive monovalent cations, B is one or more of Pb, Sn, Ge, Cu, Mn transition metal ions or rare earth ions, and X is one or more of Cl, Br, I negative monovalent halogen ions.
3. A method for preparing the mesoporous oxide confined growth multi-level coated perovskite nanomaterial according to claim 1 or 2, characterized in that: The following steps are involved: Step 1: preparing mesoporous oxide nanomaterials; Step 2: Obtaining mesoporous oxide confined growth all-inorganic perovskite nanomaterials by high temperature calcination, including the following processes: Step 2.1: Prepare precursor solution; Step 2.2: mixing the mesoporous oxide nanomaterial with the precursor solution, so that the mesoporous oxide nanomaterial fully absorbs the perovskite precursor; Step 2.3: growing perovskite nanocrystals in the micropores of the mesoporous oxide through a high temperature calcination method to obtain a mesoporous oxide confined growth all-inorganic perovskite nanomaterial; Step 3: Seal the obtained mesoporous oxide confined growth all-inorganic perovskite nanomaterial, and wash and dry the sealed material to obtain the mesoporous oxide confined growth multi-level coated perovskite nanomaterial.
4. The method according to claim 3, characterized in that: The mesoporous oxide nanomaterial in step 1 is SiO2, Al2O3, ZrO2, TiO2 or ZnO oxide nanomaterial prepared by sol-gel method, coprecipitation method, template method or spray pyrolysis method, and the size of the mesoporous oxide nanomaterial is about 50 to 200 nm.
5. The method according to claim 3, characterized in that: In step 2, high temperature calcination is performed by a one-step method, including the following processes: Step 2.1: Compare AX with B (II) X2 or B (IV) X4 is dissolved in a hot aqueous solution in a certain proportion to obtain a precursor solution; Step 2.2: mixing the mesoporous oxide nanomaterial with the precursor solution, so that the mesoporous oxide nanomaterial fully absorbs the perovskite precursor; Step 2.3: Dry the mesoporous oxide nanomaterial that adsorbs the perovskite precursor and grind it into powder. Then, according to the transition temperature of the perovskite material, calcine in steps to decompose the perovskite precursor in the micropores of the mesoporous oxide and form perovskite nanocrystals in situ, thereby obtaining a mesoporous oxide confined growth all-inorganic perovskite nanomaterial.
6. The method according to claim 5, characterized in that: When the high temperature calcination is carried out by one-step method, when the molar ratio in step 2.1 is AX:B (II) When X2=1:2, AB2 is synthesized (II) X5 wrapped AB (II) X3; when the molar ratio in step 2.1 is AX:B (II) When X2=4:1, A4B is synthesized (II) X6 coated AB (II) X3; when the molar ratio in step 2.1 is AX:B (IV) When X4=2:1, A2B is synthesized (IV) X6 coated AB (II) X 3。 7. The method according to claim 3, characterized in that: In step 2, high temperature calcination is performed using a two-step method, including the following processes: Step 2.1: Replace AX and B (II) X2 was dissolved in hot water at a molar ratio of 1:1 to prepare AB (II) A perovskite precursor solution of component X3 is used as a first precursor solution; Then AX and B (II) X2 was dissolved in a hot water solution at a molar ratio of 4:1 to prepare the vacancy-ordered double perovskite A4B. (II) X6 precursor solution as the second precursor solution; or AX and B (II) X2 was dissolved in a hot water solution at a molar ratio of 1:2 to prepare the vacancy-ordered double perovskite AB2 (II) X5 precursor solution, serving as a second precursor solution; Or AX and B (IV) X4 was dissolved in a hot water solution at a molar ratio of 2:1 to prepare the vacancy-ordered double perovskite A2B (IV) X6 precursor solution, serving as a second precursor solution; Step 2.2: Add the mesoporous oxide nanomaterial to the first precursor solution and continue stirring to allow the mesoporous oxide to adsorb sufficient AB. (II) X3 component perovskite precursor; adsorbs AB (II) The mesoporous oxide nanomaterial of the X3 component perovskite precursor is dried and kept at a set temperature for a set time and then cooled to room temperature, and then the powder cooled to room temperature is added to the second precursor solution and continuously stirred; Step 2.3: The mesoporous oxide nanomaterial taken out from the second precursor solution is dried and ground into powder, and then according to the transition temperature of the perovskite material, the perovskite precursor is decomposed in the mesoporous oxide microchannels through step-by-step calcination to form perovskite nanocrystals in situ, thereby obtaining a mesoporous oxide confined growth all-inorganic perovskite nanomaterial.
8. The method according to claim 3, characterized in that: In step 3, a high-temperature sealing strategy is used to seal the mesoporous oxide confined growth all-inorganic perovskite nanomaterial; the high-temperature sealing strategy is to use the high-temperature melting collapse of the oxide to perform in-situ sealing, or to pre-embed the mesoporous oxide with a low-temperature molten salt and then melt and collapse to perform in-situ sealing.
9. The method according to claim 3, characterized in that: In step 3, chemical etching is used to seal the pores of the mesoporous oxide confined growth all-inorganic perovskite nanomaterial.
10. An application of the mesoporous oxide confined growth multi-level coated perovskite nanomaterial according to claim 1 in the preparation of fluorescent ink, color conversion Micro LED and fluorescence conversion photovoltaic cell.
Citation Information
Patent Citations
Method for preparing all-inorganic perovskite light-emitting diode active layer
CN109713100A
Method for realizing reversible conversion of halogen perovskite nanocrystal
CN109987625A
Preparation method of perovskite nanoparticles with dual protection of channel confinement-shell layer isolation
CN110205110A
Preparation method of semiconductor nanocrystalline fluorescent material, semiconductor nanocrystalline fluorescent material prepared by method and application of semiconductor nanocrystalline fluorescent material
CN110734758A
Cs4PbBr6 / CsPbBr3 perovskite nanocrystalline scintillation powder and preparation method of Cs4PbBr6 / CsPbBr3 perovskite nanocrystalline scintillation powder
CN110734765A